2017
DOI: 10.1002/cphc.201601380
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Growth of Gold Nanostars: Effect of Spike Length on SERS Signal Enhancement

Abstract: Two different types of gold nanostars (Au NS), namely, short-spiked nanostars (SSNS) and long-spiked nanostars (LSNS), are prepared by using a hexagonal lyotropic liquid-crystalline (LLC) phase as a template. The formation, size and length of spikes or arms of the resultant Au NS are controlled by preparation in either a hexagonal LLC phase or an isotropic phase. These NS are anchored onto indium tin oxide (ITO) electrodes through a self-assembled monolayer of 3-mercaptopropyltrimethoxysilane, which acts as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 45 publications
(156 reference statements)
0
24
0
Order By: Relevance
“…Gold nanostars with their spike tips are of special relevance in this eld. [16][17][18][19] Liz-Marzan et al have shown that a Raman active molecule, sandwiched between the spike tip and a plasmonic surface, can enhance the SERS signal up to two orders of magnitude. 19 Not only the sharpness of the tips is of relevance, but also the arrangement of the spikes to each other which tunes the plasmon resonance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gold nanostars with their spike tips are of special relevance in this eld. [16][17][18][19] Liz-Marzan et al have shown that a Raman active molecule, sandwiched between the spike tip and a plasmonic surface, can enhance the SERS signal up to two orders of magnitude. 19 Not only the sharpness of the tips is of relevance, but also the arrangement of the spikes to each other which tunes the plasmon resonance.…”
Section: Introductionmentioning
confidence: 99%
“…19 Not only the sharpness of the tips is of relevance, but also the arrangement of the spikes to each other which tunes the plasmon resonance. Sheen Mers et al studied the effect of spike length on the SERS signal enhancement 18 and Atta et al 10 investigated the seed mediated growth of 6-branched gold nanostars with very thin spikes up to a length of 100 nm. The interplay of surfactant, ascorbic acid (AA), AgNO 3 and seed concentrations are of high importance for the crystallization of the spikes.…”
Section: Introductionmentioning
confidence: 99%
“…A library of colloidal NPs with various geometries (nanorods 26 , 27 , nanotriangles 28 , nanocages 29 and nanostars 30 , 31 , 32 ) and different sizes are under research. For instance 26 , nanorods with similar aspect ratios but different sizes show distinct SERS properties.…”
Section: Factors Affecting Sers Enhancementmentioning
confidence: 99%
“…A direct consequence of such strong confinement of the electromagnetic fields is the generation of intense signals in Raman spectra of the molecules that are located near the NPs . This phenomenon, called as surface enhanced Raman scattering (SERS), is widely used in ultra‐sensitive detection of molecules . For SERS and other applications, it remains a formidable challenge to generate such functional heterostructures over large surface areas with high yields at low costs.…”
Section: Introductionmentioning
confidence: 99%
“…[8] This phenomenon, called as surface enhanced Ramans cattering (SERS), is widely used in ultra-sensitive detection of molecules. [15,16] For SERS and other applications, it remains af ormidable challenge to generate such functional heterostructures over large surface areas with high yields at low costs. This work reports scalable, low-cost,a nd simple fabrication of plasmonic heterostructures consisting of gold nanoparticles (NPs) of different sizes to generate intense hot-pots over large areas to serve as substrates for molecular sensing in SERS applications.…”
Section: Introductionmentioning
confidence: 99%